Molecular angiogenic events of a two‐herb wound healing formula involving MAPK and Akt signaling pathways in human vascular endothelial cells. Issue 4 (11th June 2013) - Liu, Cheuk‐Lun; Tam, Jacqueline Chor Wing; Sanders, Andrew J.; Ko, Chun‐Hay; Fung, Kwok‐Pui; Leung, Ping‐Chung; Harding, Keith G.; Jiang, Wen G.; Lau, Clara Bik‐San
Abstract The emergence of electric cell‐substrate impedance sensing (ECIS) technology has provided new insight in advanced cell behavioral study by its nanometer sensitivity, precise electrical wounds generation, and high reproducibility that can be monitored in real time in a noninvasive way. However, little is known regarding pro‐angiogenic agents in wound healing studies using endothelial cells evaluated with ECIS technology. Our previous studies showed a prominent wound healing effect of a two‐herb formula (NF3) comprising of Astragali Radix and Rehmanniae Radix in a rat chronic wound model through actions including angiogenesis. Here we further investigated the angiogenic effect and its underlying molecular mechanism through proliferation, motility, and tubule formation of human vascular endothelial cells (HECV) using ECIS technology. It was first shown that HECV treated with NF3 had a higher resistance than that of control using ECIS cell attachment and cell migration model (p < 0.01). We further validated in a scratch assay that NF3 treatment significantly stimulated HECV cell migration (p < 0.01–0.05). Also, NF3‐treated HECV were observed to develop into a significantly more branched tubular structure when compared with control (p < 0.05–0.01). Meanwhile, Western blot analysis of NF3‐treated HECV revealed the activated expression of p‐Akt, and mitogen‐activated protein (MAP) kinases for p‐ERK, p‐p38, and p‐JNK. We propose that the effect of NF3 in the promotion of endothelial cell migration and tubule formation could be mediated through pathways involving p‐Akt and activated MAP kinases. Hence, we demonstrated the complexity of the angiogenic effect activated by NF3 molecularly and functionally. NF3 treatment could offer therapeutic value to chronic wound healing for its pro‐angiogenic efficacy.